Informative promotional outcome on school teachers’ knowledge about emergency management of dental trauma - Pujita, Chada (Medknow Publications & Media Pvt Ltd, 2013)
AIM: To assess awareness of school teachers concerning the emergency management of traumatized teeth. MATERIALS AND METHODS: This is a prospective intervention study conducted with 1000 teachers (500 urban, 500 rural) randomly selected from the entire government and private, primary (elementary) as well as secondary (high) schools of Nellore district of Andhra Pradesh, India. Study was carried out in three phases; the first phase being an initial survey conducted to assess the existing knowledge of teachers on management of traumatic injuries by using self-administered questionnaire. This was followed by a comprehensive informative promotion regarding the initial management of the traumatic dental injuries for the teachers. A post-promotion follow-up review was conducted 3 months later to evaluate the effect of the informative promotion, using the same set of questionnaires. Study was completed over a period of 9 months. STATISTICAL METHODS: Data analysis was done using SPSS software version 14.0, and Chi-square test was used to compare the knowledge of teachers prior to and after the informative promotion. The level of significance was set at P ≤ 0.05. RESULTS: The teachers’ overall knowledge with respect to the emergency management of the traumatic injuries was deficient and significant differences were found in the knowledge of teachers before and after the informative promotion. CONCLUSION: Informative promotion programs to improve the knowledge and awareness of this group of community, who are generally the first line of assistance in case of dental trauma in schools, are mandatory.